Sea cucumbers: a Malaysian heritage - Hashim, Ridzwan (IIUM press, 2007)
This book was written with the specific objective of addressing the information deficiency on sea cucumbers and gamat found in Malaysian coastal waters. Most of the data presented here are based on the results of scientific studies and publications by the author together with other researchers and students under his supervision either directly or indirectly. They are also the fruits of hardship that the writer experienced during his journey of discovery, which began with his initial study of holothuroids in Sabah in early 1983. The author raises the problem of confusion in species identification and suggets several new methods in order to resolve it. The book also discusses the involvement of sea cucumber and gamat-based industries including suppliers, manufacturers, and distributors in efforts to highlight the benefits of this marine creature as a food source and therapeutic ingredients. The development of such industries will definitely support local fisherman by providing them with extra sources of income apart from creating valuable job opportunities for other groups. The author, who is a consultant for one of the companies involved, also describes some of the difficulties faced by producers. It is the author's hope that this small book will be useful to researchers, related agencies, as well as sea cucumber and gamat producers and manufacturers in a concerted endeavour industries related to this natural marine heritage.